Agriculture Finance in Kosovo : Creating an Agri-Finance Market - International Finance Corporation (International Finance Corporation, Pristina, Kosovo, 2019)
The study, conducted assesses the current state of agricultural finance in the Republic of Kosovo (Kosovo) and determine ways to improve the provision of finance to Kosovo's growing agricultural economy. The study is aimed at informing the full range of stakeholders about the best options to scale up financial services for agriculture. The study relies on data from available statistics as well as on individual and group discussions with stakeholders. Kosovo's business environment is improving, despite slow advancement in the capacity and function of the public institutions responsible for providing guidance and direction to the industry. Government focus on the World Bank (WB) Doing Business indicators has produced encouraging results. According to the Doing Business 2018 report, Kosovo is currently ranked 40th in the world, up from 126th in 2012, a leap of 86 places. In ease of starting a business, Kosovo very substantially improved its ranking, by 160 places. A law on strategic investments is under consideration, and attention is being given to support public institutions that improve the business environment, such as the Business Registration Agency, which ultimately will support investors. These developments are taking place in an economy marked by high general unemployment (30.5 percent) and very high youth unemployment (52.7 percent). The public sector remains the dominant employer and pays higher wages on average than he private sector. The supply of skilled workers is insufficient to satisfy private sector demand. Small and medium enterprises dominate the economic landscape; while these are increasing in number, few grow into larger entities.